1994
DOI: 10.1007/bf00232933
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of pigeonpea (Cajanus cajan) from cotyledonary node via multiple shoot formation

Abstract: Plant regeneration, which is the major limiting factor for transformation of Cajanus cajan, has been obtained via multiple shoot formation from the cotyledonary node region of seedlings germinated on MS medium containing 2 mgl(-1) 6-benzylaminopurine. A mass of multiple shoot-initials formed at the axillary bud region of the cotyledonary node of the seedlings within two weeks. The cotyledonary node along with the mass of shoot-initials excised from the seedling, continued to form new shoot-initials on MS mediu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 10 publications
1
49
1
Order By: Relevance
“…On the other hand, the explants cultured on <0.5 mg L −1 and >0.5 mg L −1 BAP showed significantly low shoot bud elongation. Furthermore, alteration in media composition (Malik and Saxena 1992b;Shiva Prakash et al 1994), substitution of plant growth regulators (Mohamed et al 1991;Nagi et al 1997), and changes in light conditions had a significant effect on shoot elongation. Franklin et al (2000) observed that the incubation of embryonal axes of pigeon pea, under light-dark conditions, though favored the shoot bud formation, was less efficient for elongation.…”
Section: Shoot Bud Elongationmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the explants cultured on <0.5 mg L −1 and >0.5 mg L −1 BAP showed significantly low shoot bud elongation. Furthermore, alteration in media composition (Malik and Saxena 1992b;Shiva Prakash et al 1994), substitution of plant growth regulators (Mohamed et al 1991;Nagi et al 1997), and changes in light conditions had a significant effect on shoot elongation. Franklin et al (2000) observed that the incubation of embryonal axes of pigeon pea, under light-dark conditions, though favored the shoot bud formation, was less efficient for elongation.…”
Section: Shoot Bud Elongationmentioning
confidence: 99%
“…Mehta and Mohan Ram (1980) reported that higher concentration of BAP induced direct shoot regeneration from the cotyledonary surface. While low concentrations of BAP favored the development of shoot buds from the pre-existing meristems (Shiva Prakash et al 1994;Ignacimuthu et al 1997). However, higher number of viable plants were regenerated on KIN medium in several cereal crops (Bhaskaran and Smith 1990).…”
Section: Shoot Bud Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of intact seedling method in the propagation of multipurpose plant species provides timely supply of plant materials required for the isolation of drugs by the pharmaceutical industries without depleting natural plant resources as well as for reforestation of degraded and exploited lands. Several authors (Malik et al, 1993;Prakash et al, 1994;Bhuyan et al, 1997;Arya et al, 1999;Das et al, 1999;Hussain et al, 2008) have reported the use of intact seedling method in several medicinally and economically important plant species (Lathyrus cicera, Cajanus cajan, Murraya koenigii, Dendrocalamus asper, Litchi chinensis and Sterculia urens) for quick germplasm production and conservation.…”
mentioning
confidence: 99%
“…In vitro regeneration by organogenesis using diverse explants like leaf discs (Kumar et al, 1983;Eapen and George, 1993;George and Eapen, 1994;Eapen et al, 1998;Geetha et al, 1998;Dayal et al, 2003), cotyledons (Kumar et al, 1983;Mehta and Mohan, 1980;Kumar et al, 1984;Sarangi and Gleba, 1991;Naidu et al, 1995;Srinivasan et al, 2004;Chandra et al, 2003), cotyledonary nodes (Geetha et al, 1998;Shiva et al, 1994) and embryonal axes (George and Eapen, 1994;Sarangi and Gleba, 1991;Naidu et al, 1995;Franklin et al, 2000;Mohan and Krishnamurthy, 1998) has been reported. More than 50 diverse genotypes have been attempted for regeneration via organogenesis to develop suitable regeneration protocol amenable to transformation with desired genes (Krishna et al, 2010).…”
mentioning
confidence: 99%